Cytotoxicity of layered metal phosphorus chalcogenides (MPXy) nanoflakes; FePS3, CoPS3, NiPS3 - Latiff, Naziah M. (2020)
Metal phosphorus chalcogenides is a new class of 2D materials that have shown interesting semiconducting, electronic, anisotropic, magnetic, dielectric, structural and optical properties. Recently, NiPS3, FePS3 and CoPS3 in particular have been highlighted for promising potential in important energy applications such as electrocatalysts for water splitting and hydrogen storage. However, little is known about the toxicological hazards that they may pose on humans. Here, we investigated the cytotoxicity of NiPS3, FePS3 and CoPS3 on human lung carcinoma cells (A549) and normal human bronchial cells (BEAS-2B) to address this concern. Upon treatment of these cells with different MPXY materials, we determined the remaining cell viability using water soluble tetrazolium salt (WST-8) assay. We found that CoPS3 was most toxic followed by FePS3 with intermediate toxicity while NiPS3 showed the lowest toxicity among the three materials tested for both cell lines. When viewed with other layered materials, these MPXY samples present comparable toxicities with transition metal dichalcogenides and black phosphorus at low concentrations.